Shock wave enhanced emission photoacoustic streaming (SWEEPS): An alternative to conventional irrigation in endodontic treatment - Jordana, Jesslyn; Nicholas Tandean, Jason; Fiona Salim, Jennifer; Cahyani, Febriastuti; Sampoerno, Galih (Conservative Dentistry Journal, 2022)
Background: Irrigation is an essential step in root canal treatment (RCT). However, the complex structure of the root canal can limit the penetration of irrigants, causing RCT failure. Shock wave enhanced emission of photoacoustic streaming (SWEEPS) has been developed to improve root canal cleaning by increasing the penetration of irrigants. SWEEPS utilized the Er:YAG laser to generate micropulse, producing bubbles delivered in liquid, causing powerful photodynamic streaming. However, its superiority compared to conventional irrigation remains unclear. Thus, we aim to review the available evidence to assess the benefits of SWEEPS over conventional irrigation. Purpose: This study aims to review the available evidence to assess the benefits of SWEEPS over conventional irrigation. Reviewa: Article searches were conducted on Pubmed, ScienceDirect, EBSCOhost, and ProQuest using SWEEPS and root canal irrigation as keywords. Articles were included if they aim to assess the benefits of SWEEPS over conventional irrigation in removing smear layer, debris, pulp tissues, or bacteria. A total of 833 articles were initially retrieved from systemic search of literature and 6 articles following inclusion criteria were included in the review. Out of 6 articles, 4 articles suggested that SWEEPS could increase the removal of smear layer, debris, pulp tissues, and bacteria in the root canal compared to conventional irrigation. However, 2 articles found contradictory results, in which SWEEPS and conventional irrigation had similar outcomes in terms of penetration depth and could not completely eradicate biofilm. Conclusion: This review suggests that SWEEPS offers more benefits over conventional irrigation since it can improve the removal of smear layer, debris, pulp tissues, and bacteria in the root canal.